Experience of Implementing a Cross-Border Primary Care Cooperation Project During the COVID-19 Pandemic: A Qualitative Study - Silvia Caristia; Erica Busca; Sara Campagna; Erika Bassi; Alberto Dal Molin (Nursing Reports)
Background/Objectives: The REACtion project was developed to provide nursing care to older adults at home within the primary care setting. The COVID-19 pandemic posed significant challenges to its implementation, acting both as a barrier and an opportunity. Although several studies have explored healthcare innovation during emergencies, there remains a need for strategic insights to guide real-world implementation efforts. This study aims to explore how the COVID-19 pandemic influenced the implementation of the REACtion project and identify the strategies adopted to ensure continuity and effectiveness in achieving its goals despite the challenges posed by the health emergency. Methods: A qualitative descriptive study was conducted. Semi-structured interviews were carried out with nine project stakeholders, including nurses and researchers, between April and May 2023. The interviews were transcribed verbatim, read in-depth, and analyzed using content analysis to identify perceived barriers, facilitators, and strategies adopted during the project. Results: The pandemic shifted priorities from routine care to emergency health activities. Barriers to project implementation included social distancing, disruptions in the decision-making processes, and a general decline in community welfare. Despite these obstacles, the COVID-19 context underscored the central role of Family and Community Nurses in proactive primary care. Stakeholders adopted relationship-based strategies, addressed workforce shortages, and implemented measures to mitigate personal fatigue. Conclusions: The implementation of innovative nursing interventions during emergencies requires adaptability, collaboration, and context-sensitive approaches. Strengthening stakeholder engagement and leveraging professional roles within the community are essential to overcoming barriers and seizing opportunities in crisis contexts.